2D Boron Sheets: Structure, Growth, and Electronic and Thermal Transport Properties. (21st October 2019) - Li, Dengfeng; Gao, Junfeng; Cheng, Peng; He, Jia; Yin, Yan; Hu, Yanxiao; Chen, Lan; Cheng, Yuan; Zhao, Jijun
Abstract: The structures of boron clusters, such as flat clusters and fullerenes, resemble those of carbon. Various two‐dimensional (2D) borophenes have been proposed since the production of graphene. The recent successful fabrication of borophene sheets has prompted extensive researches, and some unique properties are revealed. In this review, the recent theoretical and experimental progress on the structure, growth, and electronic and thermal transport properties of borophene sheets is summarized. The history of prediction of boron sheet structures is introduced. Existing with a mixture of triangle lattice and hexagonal lattice, the structures of boron sheets have peculiar characteristics of polymorphism and show significant dependence on the substrate. Due to the unique structure and complex BB bonds, borophene sheets have many interesting electronic and thermal transport properties, such as strong nonlinear effect, strong thermal transport anisotropy, high thermal conductance in the ballistic transport and low thermal conductivity in the diffusive transport. The growth mechanism and synthesis of borophene sheets on different metal substrates are also presented. The successful prediction and synthesis will shed light on the exploration of new novel materials. Besides, the outstanding and peculiar properties of borophene make them tempting platform for exploring novel physical phenomena and extensive applications. Abstract : The recent successful fabrication of borophene sheets has prompted extensive research. Here, the recent theoretical and experimental progress on the structure, growth, and electronic and thermal transport properties of borophene sheets is summarized. Recent theoretical studies on the thermal stability, ballistic thermal transport, diffusive thermal transport, and abnormal strain effect of borophene are discussed and compared with those of graphene.